Women, Gender, and Print Culture in Eighteenth-Century Britain : Essays in Memory of Betty Rizzo. - Berg, Temma (Lehigh University Press, 2013)
This edited collection, a tribute to eighteenth-century scholar Betty Rizzo, builds on her important work on epistolarity, print culture, and women's relationships in life and literature. Treating topics ranging from Austen's novels to the work of the current artist Sophie Calle, the book will appeal to students and scholars of eighteenth-century British literature and culture and to those interested in women's writing and women's relationships in the eighteenth century-and today-and in feminist literary history.